Learning Management System sebagai Cloud Storage dalam Pembelajaran berbasis Digital pada Jenjang Pendidikan Tinggi - Lelahester Rina; Agus Sugiarto (Kelola: Jurnal Manajemen Pendidikan, 2022)
The purpose of this research is to analyze the acceptance of the Learning Management System as the Cloud Storage for students in digital-based learning at Universitas Kristen Satya Wacana. The research is conducted using a descriptive quantitative research design. The data is acquired from 250 students of Universitas Kristen Satya Wacana who participate in the online lesson using the Cloud Storage in the Learning Management System. The technique of data collection is by using a closed questionnaire through random sampling. The acceptance of Cloud Storage usage is measured using Technology Acceptance Model (TAM). The result of the research shows a high outcome. During online lessons, the students use Cloud Storage in LMS which is integrated with the data storage feature in form of lesson materials, assignment files, teacher-students discussion forums, presence lists, meeting links, etc. Cloud Storage usage in LMS provides convenience, and benefit gain so that it can increase class performance which is effective and efficient, convenient, and fun, and it will trigger the interest in actual use of digital platforms.